Effects of stimbiotic supplementation on gut health, immune response, and intestinal microbiota in weaned piglets challenged with E. coli - Song, Dongcheol; Lee, Jihwan; Kwak, Woogi; Oh, Hanjin; Chang, Seyeon; An, Jaewoo; Cho, Hyunah; Park, Sehyun; Jeon, Kyeongho; Cho, Jinho (Frontiers in Veterinary Science, 2023)
The objective of this study was to determine the effects of dietary stimbiotic (STB) supplementation on growth performance, intestinal morphology, immune response and intestinal microbiota in weaned piglets. A total of 24 (Duroc × Yorkshire × Landrace) weaned pigs (initial body weight of 8.01 ± 0.38 kg and 28 ± 3 d old), were assigned to 4 treatments with 6 replicates per treatment. Pigs were housed in individual pens for 17 days, including 5 days adaption period and 12 days after the first Escherichia coli (E. coli) challenge. The experiment was conducted in a 2 × 2 factorial arrangement of treatments consisting of two levels of challenge (challenge and non-challenge) and two levels of STB (0 and 0.5 g/kg diet). Supplementations of STB 0.5 g/kg improved the gain to feed ratio (G:F) (P < 0.05) in piglets challenged with shiga toxigenic E. coli (STEC). STB supplementation decreased (P < 0.05) white blood cells, neutrophils, lymphocytes, and expression levels of tumor necrosis factoralpha and interleukin-6. Supplementation of STB improved (P < 0.05) the lymphocytes and neutrophils in piglets challenged with STEC on 12 dpi. Supplementation of STB also improved (P < 0.05) the villus height to-crypt depth ratio of ileum in piglets challenged with STEC. Supplementation of STB increased (P < 0.05) the expression levels of claudin-1 of ileum. In genus level, supplementation of STB increased (P < 0.001) the abundance of prevotella compared to non-supplementation of STB groups in pre-inoculation period. Also, supplementation of STB decreased (P < 0.05) the abundance of Faecalibacterium and Eubacterium_coprostanoligenes_group compared to non-supplementation of STB groups in post-inoculation period. In phylum level, supplementation of STB increased (P < 0.05) the abundance of Desulfobacterota and Fibrobacterota in pre-inoculation period. E. coli challenge increased the abundance of Fibrobacterota compared to non-challenged group in postinoculation period.In conclusion, these findings indicated that STB supplementation could alleviate a decrease of the performance, immune response, and inflammatory response in piglets induced by the STEC challenge.